Extreme temperatures modulate gene expression in the airway epithelium of the lungs in mice and asthma patients - Makrufardi, Firdian; Peng, Syue-Wei; Chung, Kian Fan; Chadeau-Hyam, Marc; Lee, Kang-Yun; Hsiao, Ta-Chih; Ho, Kin-Fai; Rusmawatiningtyas, Desy; Murni, Indah Kartika; Arguni, Eggi; Wang, Yuan-Hung; Ho, Shu-Chuan; et al. (Frontiers in Medicine, 2025)
BackgroundThe objective of this study was to examine the effects of extreme temperatures on the gene signature and pathways of airway epithelial cells in mice and asthma patients.MethodsWe investigated the effects of temperature exposure at normal (22°C), and extreme low (10°C), high (40°C) and temperature fluctuation (40°C for 2 h followed by 10°C for next 2 h) in B6.Sftpc-CreERT2;Ai14(RCL-tdT)-D mice and pediatric and adult patient’s airway epithelial exposed to extreme temperatures.ResultsWe observed that Mmp8, Sftpb, Cxcl15 and Cd14 were significantly upregulated in airway epithelial cells in mice model. Cma1, Kit, Fdx1, Elf1a, Cdkn2aipnl, Htatsf1, Mfsd13a, Gtf2h5, Tiam2, and Trmt10c were significantly upregulated in 40°C exposure in airway epithelial cells. Sftpc, Gpr171, Sic34a2, Cox14, Lamp3, Luc7l, Nxnl, Tmub2, Tob1, and Cd3e genes were significantly upregulated in 10°C exposure group. Pediatric asthma subjects in the extreme high temperature group consistently showed decreased Wfdc21, Cib3, and Sftpc, at the same time increased Tiam2 and Cma1 expression, while in the extreme low temperature group exhibited consistently higher expression of Sftpc and Nxnl, at the same time decreased Wfdc21, Cib3, Cma1, and Dld expression. Notably, the mice in the extreme temperature fluctuation group showed decreased Wfdc21, Cib3, Gpr171, and Cttnbp2 expression, while increased Hbb-bs expression. Adult asthma subjects in the extreme temperature fluctuation group showed consistently decreased Wfdc21, Cib3, Gpr171, and Cttnbp2 expression, while increased Tiam2 and Cma1 expression. We observed that the mild, moderate, and severe asthma subject in the extreme low temperature group showed increased Tob1, Mub2, Sic34a2, Sftpc, Nxnl, Luc71, Lamp3, Gpr171, Cox14, and Cd3e expression, while in the severe asthma subjects showed increased expression in all temperature exposure group.ConclusionOur study highlights the effects of extreme temperatures on the gene signature of the airway epithelium in both mice and asthma patients. These findings suggest that extreme temperatures modulate gene expression in the airway epithelium, potentially serving as clinical indicators or biomarkers in response to climate change.